Serological, culture and molecular survey of Mycobacterium avium paratuberculosis in a goat flock in Tuscany - Galiero, Alessia; Turchi, Barbara; Pedonese, Francesca; Nuvoloni, Roberta; Cantile, Carlo; Colombani, Giuseppe; Forzan, Mario; Cerri, Domenico; Bandecchi, Patrizia; Fratini, Filippo (Folia microbiologica, 2017)
Mycobacterium avium paratuberculosis (Map) is a pathogen which causes a chronic progressive granulomatous enteritis known as paratuberculosis or Johne’s disease and it primarily affects wild and domestic ruminants. The aim of this research was to examine a flock which consisted of 294 goats and was located in Garfagnana district (Tuscany, Italy) performing ELISA tests, culture and IS900 PCR assay; direct diagnostic methods were carried out not only on bulk tank milk and cheese samples but also on individual milk and tissue specimens collected from nine subjects positive to ELISA tests. Out of 294 animals, 20 goats (6.8%) were positive to ELISA surveys. Bulk tank milk samples were negative to culture and to PCR assay carried out on the DNA extracted directly from them, while, with respect to cheese, Map was detected by culture in 2/12 (16.66%) cheeses ripened for 3–7 days, and by PCR in 2/12 (16.66%) cheeses ripened for 3–7 days and in 3/12 (25%) cheeses ripened for 45 days. Regarding individual milk samples, Map was detected by culture in 2/9 (22.22%) specimens and by PCR in 5/9 (55.55%) samples. Furthermore, Map was isolated from the intestine in 9/9 (100%) animals, from the mesenteric lymph nodes in 8/9 (88.88%) subjects, from the liver in 4/9 (44.44%) goats, from the spleen in 5/9 (55.55%) animals, while Map DNA was found in all the tissue samples analyzed. The results demonstrated the presence of paratuberculosis in a goat flock located in Garfagnana district (Tuscany, Italy).